The Effect of Food Ingredients Containing Protein on Stunting Cases in East Java - Komang, Indora Yusakobus; Ashar, Khusnul; Syafitri, Wildan (Journal of International Conference Proceedings, 2023)
Stunting is a condition in where children are experienced growth disturbances and affect them into adulthood (maturity). In the long period, stunting can cause decreasing  economic country. East Java is province that supporting the economy of Indonesia,  including the producer of foodstuffs that contain protein. Where protein is one of the micronutrients that affects cases of stunting. In fact, there are many cases of stunting in East Java. By using the data from BPS, this study wanted to determined the effect of food ingredients containing protein on stunting cases in East Java. Based on BPS data, there are seven high-protein food ingredients that are most consumed by the people in East Java. However, based on the panel data regression, there is only one food ingredient that has the effect of reducing stunting rates, it was egg consumption. By focusing on it, hopes that the government can control the prices and distribution. Therefore public can consumed it easily and cheaply.